Impact of the implementation of the AAN epilepsy quality measures on the medical records in a university hospital - Cisneros Franco, J Miguel; Díaz Torres, Marco A; Rodríguez Castañeda, Juan B; Martínez Silva, Alejandro; Gutierrez Herrera, Mildred A; San Juan, Daniel (2013)
Background: The American Academy of Neurology (AAN) suggested eight quality measures to be observed at every patient visit. The aim of this work is to compare the percentage of documentation of each measure before and after the implementation of a new worksheet in a third-level center. Methods: Quasi-experimental study including medical records filled by medical school seniors and junior residents supervised by an epileptologist. The authors surveyed 80 consecutive charts of people with epilepsy who were seen in the outpatient clinic before and after the intervention. McNemar change test was used to compare the percentages of documentation of each quality measure–i.e., seizure type and frequency, etiology, EEG, MRI/CT head scans, AED side effects, surgical therapy referral, safety counseling, preconception counseling–and physical exam. Each quality measure was considered to be fulfilled only if it was assessed and properly recorded. Results: Mean age was 35(±13) years, 55% women, mean epilepsy onset at age 18(±15), 82% presented with partial-onset seizures. The reporting rate improved for all quality measures (previous vs new), reaching statistical significance for: seizure type 80vs94% (p < 0.05), AED side effects 8vs24%, etiology 66vs88% (p < 0.01), safety counseling 5vs64%, preconception counseling 4vs20%, and physical exam 63vs94% (p < 0.001). Conclusion: A quality-oriented epilepsy worksheet led to a better practice standardization and documentation of AAN standards for diagnostic and counseling purposes. Further evaluations should be undertaken to assess the impact on medical education and patient care.